Mapping dan Strategi Pengembangan Potensi Ekonomi Berbasis Budaya Lokal di Provinsi Riau - Mahyarni, .; Meflinda, Astuti; Bustam, Nurhasanah; Tanjung, Hasrudi (Jurnal Aplikasi Manajemen, 2015)
The aims of the study are (1) to know the mapping potential of local culture-basedeconomy. (2) To know the potential economic development strategy based on local culturein promoting community empowerment. This study is a descriptive qualitative research, byusing survey method. The results showed that the mapping about food products, are categorizedinto (1) mapping of typically food products in Riau with characteristic of ingredientsfrom Riau, (2) mapping typical food products in Riau made from common base, and (3)mapping of food products made from common areas and can be produced in several areas.Each area/region in general has the potential food products that are unique and distinctivethat can be raised and developed. Mapping towards these products could be concluded thatthere are products that have the potential to be developed into national and internationalmarkets and only a small part of products that has the potential to fill the local market. Thestrategy used in developing food products in this study using SWOT analysis as the basis fordesigning the strategy and working program that covering the assessment of strengths,weaknesses, opportunities and, challenges.